Association of Pollinators of Different Species of Oil Palm with the Metabolic Profiling of Volatile Organic Compounds. Issue 6 (20th May 2019) - Alves Filho, Elenilson G.; Brito, Rafaela S.; Rodrigues, Tigressa Helena S.; Silva, Lorena Mara A.; de Brito, Edy S.; Canuto, Kirley M.; Krug, Cristiane; Zocolo, Guilherme J.
Abstract: The development of studies on emissions of volatile organic compounds (VOCs) by inflorescence of oil palms deserves a special attention regarding the importance to reproduction success and for increase of production. This study aimed to evaluate metabolic profiling of VOCs expelled by male and female inflorescences of different oil palm species (African oil palm, Amazonian Caiaué and the interspecific hybrid BRS‐Manicoré), associating the composition variability with main pollinators to improve the comprehension of the plant−insect relationship. The phenylpropanoids, terpenoids and the aliphatic hydrocarbons were predominant classes detected in inflorescences of oil palms and the major compound was estragole. This result may be correlated with attraction of Elaidobius pollinators, since these insects were not attracted by Caiaué, which emitted estragole only in trace amounts. However, Caiaué and the hybrid species were visited by other native species whose frequencies were low and their success as pollinators could not be expected. Abstract :